The 'snowflakes' of modern society: a qualitative investigation of female university students’ anxiety about adulting - Talbot, A; O'Reilly, M; Dogra, N (Emerald, 2023)
Purpose: To explore the anxiety of university students. We note that the rhetoric of the snowflake is frequently invoked in lay discourse to characterise a generation of young people as overly sensitive. This misleading conceptualisation is potentially stigmatising.